Method and device for preparing sodium fluorosilicate from by-product fluorosilicic acid of wet-process phosphoric acid
Through the reaction crystallization method of the by-product of fluosilicate and sodium sulfate by-product of wet phosphoric acid, the polytetrafluoroethylene film loaded with sodium sulfate particles was solved, and the problem of low sodium salt utilization and insufficient purity in the existing production of sodium fluosilicate was solved. , high purity and high utilization rate of sodium fluorosilicate production is achieved.
Patent Information
- Application Number
- CN202411329752.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-24
AI Technical Summary
In the existing sodium fluorosilicate production methods, the sodium salt utilization rate is insufficient and the finished product has a low purity, so a production solution with both high utilization rate and high purity is required.
The reaction crystallization method of wet phosphoric acid by-product fluorosiliic acid and sodium sulfate is carried out by the polytetrafluoroethylene film loaded with sodium sulfate particles as a carrier, and the hydrophilicity of the polytetrafluoroethylene film is used. and microporous structure, improve the utilization rate of sodium sulfate and the purity of sodium fluorosilicate.
The high purity of sodium fluorosilicate (99.97%) and high utilization rate (99.76%) were achieved, while the utilization rate of sodium sulfate (99.10%) was improved, the wastewater discharge was reduced and the easy crystallization phenomenon was avoided.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium fluorosilicate preparation, and in particular to a method and a device for preparing sodium fluorosilicate by producing fluorosilicic acid as a byproduct of wet-process phosphoric acid. Background Art
[0002] In addition to fluorite, the fluorine sources with utilization value in nature mainly come from phosphate rock (fluorine content is 2%-4%). The fluorine in phosphate rock escapes in the form of gaseous HF and SiF4 during the production of wet phosphoric acid and ordinary superphosphate, and is absorbed by water and converted into a 10%-40% fluorosilicic acid solution, which can be used as a raw material to prepare a variety of fluoride salts. Among them, sodium fluorosilicate has a wide range of uses, mainly in construction, building materials industry, enamel solvent, glass opalizer, wood preservative, industrial detergent, etc. In addition, sodium fluorosilicate is also widely used in the fields of pharmaceuticals and drinking water. In addition, sodium fluorosilicate is also a raw material for the production of silicon dioxide, artificial cryolite, sodium fluoride, and ammonium fluoride.
[0003] The sodium fluorosilicate currently produced mainly comes from phosphorus chemical enterprises. After the fluorosilicic acid produced by the tail gas absorption of the wet phosphoric acid production line reacts with sodium salt, it is filtered, washed and dried to obtain a sodium fluorosilicate product. The current production method of sodium fluorosilicate can be divided into sodium chloride method and sodium sulfate method according to different raw materials. In theory, sodium fluorosilicate can also be produced with other sodium salts, but due to the high production cost of other sodium salts, it is rarely used in industry. Sodium sulfate method and sodium chloride method are adopted by most manufacturers due to their low price and mature technology. The commonly used sodium sulfate method production process needs to adopt the fixed acid salt adjustment method, that is, the amount of fluorosilicic acid is unchanged when feeding, and the amount of acid is matched by adjusting the excess coefficient of salt. Although the utilization rate of fluorosilicic acid can be improved, the utilization rate of sodium salt is low, and the finished product purity of the fluorosilicic acid produced is low.
[0004] Therefore, there is a need for a finished sodium fluorosilicate solution that can achieve high utilization rates of fluorosilicic acid and sodium salt and has high purity. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a method and device for preparing sodium fluorosilicate from wet-process phosphoric acid as a by-product of fluorosilicic acid, so as to solve the problems of insufficient sodium salt utilization and low purity of finished sodium fluorosilicate in the prior art.
[0006] Based on the above purpose, the first aspect of the present invention provides a method for preparing sodium fluorosilicate from wet-process phosphoric acid as a by-product of fluorosilicic acid, comprising the following steps:
[0007] The fluorosilicic acid solution produced as a byproduct of wet-process phosphoric acid is centrifuged to remove solid particles, and then the fluorosilicic acid solution after centrifugation is adjusted to have a fluorosilicic acid mass concentration of 15-25%;
[0008] Mixing the fluorosilicic acid solution with the sodium sulfate solution for a first reaction crystallization, wherein the molar ratio of fluorosilicic acid to sodium sulfate is 1:0.95-1.15;
[0009] After the primary reaction crystallization is completed, a polytetrafluoroethylene membrane loaded with sodium sulfate particles is placed to continue the secondary reaction crystallization, wherein the polytetrafluoroethylene membrane loaded with sodium sulfate particles is prepared by an impregnation method, and the amount of sodium sulfate particles added is: the molar ratio of fluorosilicic acid to sodium sulfate is 1:0.15-0.5;
[0010] The polytetrafluoroethylene membrane is taken out and recycled, and the filtrate and sodium fluorosilicate are obtained by centrifugation.
[0011] Preferably, the preparation method of the polytetrafluoroethylene membrane loaded with sodium sulfate particles is as follows: placing a polytetrafluoroethylene membrane with a pore size of 0.5-15 μm in a saturated sodium sulfate solution at 50-80°C for 1-72 hours, then taking out the polytetrafluoroethylene membrane and drying it to obtain a sodium sulfate particle loading of 100-500 g / m 2 .
[0012] Preferably, the polytetrafluoroethylene with a pore size of 0.5-15 μm is a modified hydrophilic fiber membrane, and the modification process is as follows:
[0013] S1, dissolving polyethylene glycol in water, and stirring to obtain a polyethylene glycol aqueous solution;
[0014] S2. Add polyethyleneimine dropwise to the polyethylene glycol aqueous solution while stirring at 50-80° C., wherein the molar ratio of polyethylene glycol to polyethyleneimine is 5-1:1, and continue stirring for 0.5-2 h after the addition is complete;
[0015] S3, placing the polytetrafluoroethylene hollow fiber membrane from which impurities have been removed into a mixed solution of polyethylene glycol and polyethyleneimine, and leaving it to stand for 1-5 hours;
[0016] S4, placing the polytetrafluoroethylene fiber membrane obtained in step S3 into a cross-linking solution, and reacting at 30-38° C. for 0.5-3 h, wherein the cross-linking solution is composed of acetone, acetic acid, nitric acid, ethanol and deionized water;
[0017] S5. Take out the polytetrafluoroethylene fiber membrane obtained in step S4 and clean it ultrasonically with deionized water.
[0018] Preferably, in the cross-linking liquid, the mass fraction of acetone is 1-3%, the mass fraction of acetic acid is 2-8%, the mass fraction of nitric acid is 0.1-1%, and the mass fraction of ethanol is 5-10%.
[0019] Preferably, the modification process further comprises step S6, immersing the polytetrafluoroethylene fiber membrane obtained in step S5 in a KH560 solution with a mass fraction of 1-5%, reacting at 38-50° C. for 1-5 hours, taking out, washing with deionized water and drying to obtain the hydrophilic fiber membrane.
[0020] Preferably, the crystallization temperature of the primary reaction is 25-50°C, and the reaction time is 10-100 min; the crystallization temperature of the secondary reaction is 5-20°C, and the reaction time is 10-60 min.
[0021] Preferably, the polytetrafluoroethylene membrane does not need to be cleaned when it is recycled and reused, and can be directly immersed in a saturated sodium sulfate solution to be circulated again for secondary reaction crystallization.
[0022] Preferably, the method further comprises recycling the filtrate and performing a cyclic reaction again, specifically, when the concentration of the fluorosilicic acid solution produced as a byproduct of wet-process phosphoric acid is too high, adding the filtrate to adjust the concentration of the fluorosilicic acid solution after centrifugation.
[0023] The second aspect of the present invention provides a device for preparing sodium fluorosilicate from by-product fluorosilicic acid produced by wet-process phosphoric acid, which is used to perform the method for preparing sodium fluorosilicate from by-product fluorosilicic acid produced by wet-process phosphoric acid;
[0024] The device comprises an acid treatment component, a primary reaction crystallization tank, a secondary reaction crystallization tank, a centrifugal separation component and a filtrate recovery component which are connected in sequence.
[0025] The acid treatment component comprises a fluosilicic acid solution regulating tank and a sodium sulfate solution preparation tank, wherein the fluosilicic acid solution regulating tank is used to regulate the fluosilicic acid solution after centrifugation so that the fluosilicic acid mass concentration is 15-25%, and the sodium sulfate solution preparation tank is used to prepare the sodium sulfate solution, and the fluosilicic acid solution regulating tank and the sodium sulfate solution preparation tank are respectively connected to the primary reaction crystallization tank;
[0026] The primary reaction crystallization pool is used for mixing the fluorosilicic acid solution with the sodium sulfate solution to perform primary reaction crystallization;
[0027] The secondary reaction crystallization tank is used to place a polytetrafluoroethylene membrane loaded with sodium sulfate particles into the mixed solution after the primary reaction crystallization, and continue the secondary reaction crystallization;
[0028] The centrifugal separation component is used to separate the mixed liquid flowing out of the secondary reaction crystallization pool to obtain filtrate and sodium fluorosilicate;
[0029] The filtrate recovery component is in communication with the fluosilicic acid solution regulating tank and is used for recovering and storing the filtrate and / or conveying the filtrate to the fluosilicic acid solution regulating tank.
[0030] Preferably, the secondary reaction crystallization pool is a cylindrical structure, and an agitator, a cooling device, a thermometer and a plurality of fixed plates are provided inside the pool wall; the plurality of fixed plates are provided on the inner side of the pool wall for laying and fixing the polytetrafluoroethylene membrane, and the fixed plates are a mesh structure of 80-100 mesh; the stirring speed of the agitator is 1-40rpm.
[0031] Beneficial effects of the present invention:
[0032] By taking hydrophilic polytetrafluoroethylene membrane as carrier, sodium sulfate solid particles are loaded in the micropores of polytetrafluoroethylene membrane, because the hydrophilicity of polytetrafluoroethylene membrane makes the reaction medium aqueous solution fully enter the micropores, dissolves a part of sodium sulfate particles and enters the solution to participate in the reaction, plays the role of slow-release sodium sulfate, and avoids solid sodium sulfate directly participating in the reaction. In addition, the microporous structure of polytetrafluoroethylene membrane makes the fluorosilicic acid and sodium sulfate that partly enter the micropores possibly directly react to generate sodium fluorosilicate, and micropore can effectively suppress sodium fluorosilicate crystallization. Therefore, adopt the scheme of the present invention, carry out secondary reaction crystallization, and adopt polytetrafluoroethylene membrane as carrier to make solid sodium sulfate directly participate in the reaction, both reduce wastewater discharge, avoid the phenomenon of easy crystallization, improve product purity and the utilization rate of fluorosilicic acid and sodium sulfate, the obtained sodium fluorosilicate crystal purity is up to 99.97%, the utilization rate of fluorosilicic acid is up to 99.76%, and the utilization rate of sodium sulfate is up to 99.10%. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0034] Embodiment 1:
[0035] A method for preparing a polytetrafluoroethylene membrane loaded with sodium sulfate particles comprises the following steps:
[0036] S1, dissolving polyethylene glycol in water, and stirring to obtain a polyethylene glycol aqueous solution;
[0037] S2. Add polyethyleneimine dropwise to the polyethylene glycol aqueous solution while stirring at 80° C. The molar ratio of polyethylene glycol to polyethyleneimine is 1:1. Continue stirring for 2 hours after the addition is complete.
[0038] S3, placing the polytetrafluoroethylene hollow fiber membrane from which impurities have been removed into a mixed solution of polyethylene glycol and polyethyleneimine, and leaving it to stand for 5 hours;
[0039] S4, placing the polytetrafluoroethylene fiber membrane obtained in step S3 into a cross-linking solution, and reacting at 38° C. for 0.5 h, wherein the cross-linking solution consists of acetone, acetic acid, nitric acid, ethanol and deionized water, wherein the mass fraction of acetone is 3%, the mass fraction of acetic acid is 8%, the mass fraction of nitric acid is 0.1%, and the mass fraction of ethanol is 10%;
[0040] S5, taking out the polytetrafluoroethylene fiber membrane obtained in step S4, and ultrasonically cleaning it with deionized water;
[0041] S6, immersing the polytetrafluoroethylene fiber membrane obtained in step S5 in a 5% by mass KH560 solution, reacting at 38° C. for 1 hour, taking out, washing with deionized water and drying, to obtain a hydrophilic polytetrafluoroethylene membrane with a pore size of 0.5-15 μm;
[0042] S7, placing a hydrophilic polytetrafluoroethylene membrane with a pore size of 0.5-15µm in a saturated sodium sulfate solution at 80°C for 1 hour, then taking out the polytetrafluoroethylene membrane and drying it to obtain a sodium sulfate particle loading of 400g / m 2 .
[0043] Embodiment 2:
[0044] A method for preparing a polytetrafluoroethylene membrane loaded with sodium sulfate particles comprises the following steps:
[0045] S1, dissolving polyethylene glycol in water, and stirring to obtain a polyethylene glycol aqueous solution;
[0046] S2. Add polyethyleneimine dropwise to the polyethylene glycol aqueous solution while stirring at 50° C. The molar ratio of polyethylene glycol to polyethyleneimine is 5:1. After the addition is complete, continue stirring for 0.5 h.
[0047] S3, placing the polytetrafluoroethylene hollow fiber membrane from which impurities have been removed into a mixed solution of polyethylene glycol and polyethyleneimine, and leaving it to stand for 1 hour;
[0048] S4, placing the polytetrafluoroethylene fiber membrane obtained in step S3 into a cross-linking solution, and reacting at 30° C. for 3 hours, wherein the cross-linking solution consists of acetone, acetic acid, nitric acid, ethanol and deionized water, wherein the mass fraction of acetone is 1%, the mass fraction of acetic acid is 2%, the mass fraction of nitric acid is 1%, and the mass fraction of ethanol is 5%;
[0049] S5, taking out the polytetrafluoroethylene fiber membrane obtained in step S4, and ultrasonically cleaning it with deionized water;
[0050] S6, immersing the polytetrafluoroethylene fiber membrane obtained in step S5 in a 1% by mass KH560 solution, reacting at 50° C. for 1 hour, taking out, washing with deionized water and drying, to obtain a hydrophilic polytetrafluoroethylene membrane with a pore size of 0.5-15 μm;
[0051] S7, placing a hydrophilic polytetrafluoroethylene membrane with a pore size of 0.5-15µm in a saturated sodium sulfate solution at 50°C for 72 hours, then taking out the polytetrafluoroethylene membrane and drying it to obtain a sodium sulfate particle loading of 300g / m 2 .
[0052] Embodiment 3:
[0053] A method for preparing a polytetrafluoroethylene membrane loaded with sodium sulfate particles comprises the following steps:
[0054] S1, dissolving polyethylene glycol in water, and stirring to obtain a polyethylene glycol aqueous solution;
[0055] S2. Add polyethyleneimine dropwise to the polyethylene glycol aqueous solution while stirring at 65° C. The molar ratio of polyethylene glycol to polyethyleneimine is 3:1. After the addition is complete, continue stirring for 1.5 hours.
[0056] S3, placing the polytetrafluoroethylene hollow fiber membrane from which impurities have been removed into a mixed solution of polyethylene glycol and polyethyleneimine, and leaving it to stand for 3 hours;
[0057] S4, placing the polytetrafluoroethylene fiber membrane obtained in step S3 into a cross-linking solution, and reacting at 34° C. for 2 hours, wherein the cross-linking solution consists of acetone, acetic acid, nitric acid, ethanol and deionized water, wherein the mass fraction of acetone is 2%, the mass fraction of acetic acid is 5%, the mass fraction of nitric acid is 0.5%, and the mass fraction of ethanol is 7%;
[0058] S5, taking out the polytetrafluoroethylene fiber membrane obtained in step S4, and ultrasonically cleaning it with deionized water;
[0059] S6, immersing the polytetrafluoroethylene fiber membrane obtained in step S5 in a 3% by mass KH560 solution, reacting at 44° C. for 3 h, taking out, washing with deionized water and drying, to obtain a hydrophilic polytetrafluoroethylene membrane with a pore size of 0.5-15 μm;
[0060] S7, placing a hydrophilic polytetrafluoroethylene membrane with a pore size of 0.5-15µm in a saturated sodium sulfate solution at 65°C for 37 hours, then taking out the polytetrafluoroethylene membrane and drying it to obtain a sodium sulfate particle loading of 500g / m 2 .
[0061] Embodiment 4:
[0062] A method for preparing a polytetrafluoroethylene membrane loaded with sodium sulfate particles comprises the following steps:
[0063] S1, dissolving polyethylene glycol in water, and stirring to obtain a polyethylene glycol aqueous solution;
[0064] S2. Add polyethyleneimine dropwise to the polyethylene glycol aqueous solution while stirring at 65° C. The molar ratio of polyethylene glycol to polyethyleneimine is 3:1. After the addition is complete, continue stirring for 1.5 hours.
[0065] S3, placing the polytetrafluoroethylene hollow fiber membrane from which impurities have been removed into a mixed solution of polyethylene glycol and polyethyleneimine, and leaving it to stand for 3 hours;
[0066] S4, placing the polytetrafluoroethylene fiber membrane obtained in step S3 into a cross-linking solution, and reacting at 34° C. for 2 hours, wherein the cross-linking solution consists of acetone, acetic acid, nitric acid, ethanol and deionized water, wherein the mass fraction of acetone is 2%, the mass fraction of acetic acid is 5%, the mass fraction of nitric acid is 0.5%, and the mass fraction of ethanol is 7%;
[0067] S5, taking out the polytetrafluoroethylene fiber membrane obtained in step S4, and ultrasonically cleaning it with deionized water to obtain a hydrophilic polytetrafluoroethylene membrane with a pore size of 0.5-15 μm;
[0068] S6, placing a hydrophilic polytetrafluoroethylene membrane with a pore size of 0.5-15µm in a saturated sodium sulfate solution at 65°C for 37 hours, then taking out the polytetrafluoroethylene membrane and drying it to obtain a sodium sulfate particle loading of 100g / m 2 .
[0069] Embodiment 5:
[0070] A method for preparing sodium fluorosilicate from by-product fluorosilicic acid of wet-process phosphoric acid comprises the following steps:
[0071] (1) centrifuging the fluorosilicic acid solution produced as a byproduct of wet-process phosphoric acid to remove solid particles, and then adjusting the fluorosilicic acid solution after centrifugation to a fluorosilicic acid mass concentration of 25%;
[0072] (2) mixing the fluorosilicic acid solution and the sodium sulfate solution for a single reaction crystallization at a temperature of 50° C. for 10 min and a molar ratio of fluorosilicic acid to sodium sulfate of 1:0.95;
[0073] (3) After the primary reaction crystallization is completed, the polytetrafluoroethylene membrane loaded with sodium sulfate particles prepared in Example 3 is placed, and the secondary reaction crystallization is continued. The secondary reaction crystallization temperature is 20° C. and the reaction time is 10 min. The amount of sodium sulfate particles added is: the molar ratio of fluorosilicic acid to sodium sulfate is 1:0.5;
[0074] (4) The polytetrafluoroethylene membrane is taken out for recycling and reuse, and the filtrate and sodium fluorosilicate are obtained by centrifugal separation; the polytetrafluoroethylene membrane does not need to be cleaned when it is recycled and reused, and is directly immersed in a saturated sodium sulfate solution for recirculation and secondary reaction crystallization.
[0075] Embodiment 6:
[0076] A method for preparing sodium fluorosilicate from by-product fluorosilicic acid of wet-process phosphoric acid comprises the following steps:
[0077] (1) centrifuging the fluorosilicic acid solution produced as a byproduct of wet-process phosphoric acid to remove solid particles, and then adjusting the fluorosilicic acid solution after centrifugation to a fluorosilicic acid mass concentration of 15%;
[0078] (2) mixing the fluorosilicic acid solution and the sodium sulfate solution for a single reaction crystallization at a temperature of 25° C. for 100 min and a molar ratio of fluorosilicic acid to sodium sulfate of 1:1.15;
[0079] (3) After the primary reaction crystallization is completed, the polytetrafluoroethylene membrane loaded with sodium sulfate particles prepared in Example 3 is placed, and the secondary reaction crystallization is continued. The secondary reaction crystallization temperature is 5° C. and the reaction time is 60 min. The amount of sodium sulfate particles added is: the molar ratio of fluorosilicic acid to sodium sulfate is 1:0.15;
[0080] (4) The polytetrafluoroethylene membrane is taken out for recycling and reuse, and the filtrate and sodium fluorosilicate are obtained by centrifugal separation; the polytetrafluoroethylene membrane does not need to be cleaned when it is recycled and reused, and is directly immersed in a saturated sodium sulfate solution for recirculation and secondary reaction crystallization.
[0081] Embodiment 7:
[0082] A method for preparing sodium fluorosilicate from by-product fluorosilicic acid of wet-process phosphoric acid comprises the following steps:
[0083] (1) centrifuging the fluorosilicic acid solution produced as a byproduct of wet-process phosphoric acid to remove solid particles, and then adjusting the fluorosilicic acid solution after centrifugation to a fluorosilicic acid mass concentration of 20%;
[0084] (2) mixing the fluorosilicic acid solution and the sodium sulfate solution for a single reaction crystallization at a temperature of 38° C. for a reaction time of 65 min, with a molar ratio of fluorosilicic acid to sodium sulfate of 1:1.05;
[0085] (3) After the primary reaction crystallization is completed, the polytetrafluoroethylene membrane loaded with sodium sulfate particles prepared in Example 3 is placed to continue the secondary reaction crystallization. The secondary reaction crystallization temperature is 16° C. and the reaction time is 35 min. The amount of sodium sulfate particles added is: the molar ratio of fluorosilicic acid to sodium sulfate is 1:0.1;
[0086] (4) The polytetrafluoroethylene membrane is taken out for recycling and reuse, and the filtrate and sodium fluorosilicate are obtained by centrifugal separation; the polytetrafluoroethylene membrane does not need to be cleaned when it is recycled and reused, and is directly immersed in a saturated sodium sulfate solution for recirculation and secondary reaction crystallization.
[0087] Embodiment 8:
[0088] A method for preparing sodium fluorosilicate from wet-process phosphoric acid as a byproduct of fluorosilicic acid. The preparation process of this embodiment is the same as that of Example 7, except that the polytetrafluoroethylene membrane loaded with sodium sulfate particles is prepared by the method of Example 1.
[0089] Embodiment 9:
[0090] A method for preparing sodium fluorosilicate from wet-process phosphoric acid as a byproduct of fluorosilicic acid. The preparation process of this embodiment is the same as that of Example 7, except that the polytetrafluoroethylene membrane loaded with sodium sulfate particles is prepared by the method of Example 2.
[0091] Embodiment 10:
[0092] A method for preparing sodium fluorosilicate from wet-process phosphoric acid as a byproduct of fluorosilicic acid. The preparation process of this embodiment is the same as that of Example 7, except that the polytetrafluoroethylene membrane loaded with sodium sulfate particles is prepared by the method of Example 4.
[0093] Embodiment 11:
[0094] A device for preparing sodium fluorosilicate from by-product fluorosilicic acid produced by wet-process phosphoric acid, used for carrying out the method for preparing sodium fluorosilicate from by-product fluorosilicic acid produced by wet-process phosphoric acid;
[0095] The device comprises an acid treatment component, a primary reaction crystallization tank, a secondary reaction crystallization tank, a centrifugal separation component and a filtrate recovery component which are connected in sequence.
[0096] The acid treatment component comprises a fluosilicic acid solution regulating tank and a sodium sulfate solution preparation tank, wherein the fluosilicic acid solution regulating tank is used to regulate the fluosilicic acid solution after centrifugation so that the fluosilicic acid mass concentration is 15-25%, and the sodium sulfate solution preparation tank is used to prepare the sodium sulfate solution, and the fluosilicic acid solution regulating tank and the sodium sulfate solution preparation tank are respectively connected to the primary reaction crystallization tank;
[0097] The primary reaction crystallization pool is used for mixing the fluorosilicic acid solution with the sodium sulfate solution to perform primary reaction crystallization;
[0098] The secondary reaction crystallization pool is used to place a polytetrafluoroethylene membrane loaded with sodium sulfate particles into the mixed solution after the primary reaction crystallization, and continue the secondary reaction crystallization; the secondary reaction crystallization pool is a cylindrical structure, and a stirrer, a cooling device, a thermometer and a plurality of fixed plates are arranged inside the pool wall; the plurality of fixed plates are arranged on the inner side of the pool wall for laying and fixing the polytetrafluoroethylene membrane, and the fixed plates are a mesh structure of 80-100 meshes; the stirring speed of the stirrer is 1-40rpm;
[0099] The centrifugal separation component is used to separate the mixed liquid flowing out of the secondary reaction crystallization pool to obtain filtrate and sodium fluorosilicate;
[0100] The filtrate recovery component is in communication with the fluosilicic acid solution regulating tank and is used for recovering and storing the filtrate and / or conveying the filtrate to the fluosilicic acid solution regulating tank.
[0101] Comparative Example 1:
[0102] A method for preparing sodium fluorosilicate from by-product fluorosilicic acid of wet-process phosphoric acid, which is different from Example 7 in that no secondary reaction crystallization is performed, and specifically comprises the following steps:
[0103] (1) centrifuging the fluorosilicic acid solution produced as a byproduct of wet-process phosphoric acid to remove solid particles, and then adjusting the fluorosilicic acid solution after centrifugation to a fluorosilicic acid mass concentration of 20%;
[0104] (2) mixing the fluorosilicic acid solution and the sodium sulfate solution for a single reaction crystallization at a temperature of 38° C. for a reaction time of 65 min, with a molar ratio of fluorosilicic acid to sodium sulfate of 1:1.15;
[0105] (3) Centrifugal separation is performed to obtain the filtrate and sodium fluorosilicate.
[0106] Comparative Example 2:
[0107] A method for preparing sodium fluorosilicate from by-product fluorosilicic acid of wet-process phosphoric acid, which is different from Example 7 in that fixed sodium sulfate particles are directly used for secondary reaction crystallization, and specifically comprises the following steps:
[0108] (1) centrifuging the fluorosilicic acid solution produced as a byproduct of wet-process phosphoric acid to remove solid particles, and then adjusting the fluorosilicic acid solution after centrifugation to a fluorosilicic acid mass concentration of 20%;
[0109] (2) mixing the fluorosilicic acid solution and the sodium sulfate solution for a single reaction crystallization at a temperature of 38° C. for a reaction time of 65 min, with a molar ratio of fluorosilicic acid to sodium sulfate of 1:1.5;
[0110] (3) After the first reaction crystallization is completed, sodium sulfate particles are added to continue the second reaction crystallization. The second reaction crystallization temperature is 16°C and the reaction time is 35 min. The amount of sodium sulfate particles added is: the molar ratio of fluorosilicic acid to sodium sulfate is 1:0.1. Centrifugal separation is performed to obtain a filtrate and sodium fluorosilicate.
[0111] Test example:
[0112] The purity of the finished sodium fluorosilicate products obtained in Examples 5-10 and Comparative Examples 1-2, the utilization rate of fluorosilicic acid and the utilization rate of sodium sulfate were tested respectively, and the results are shown in Table 1.
[0113] Table 1 Summary of experimental results
[0114] project Finished product purity / % Fluorosilicic acid utilization rate / % Sodium sulfate utilization rate / % Example 5 99.88 99.28 98.89 Example 6 99.90 99.15 99.01 Example 7 99.97 99.76 99.10 Example 8 99.83 99.50 98.78 Example 9 99.85 99.51 98.68 Example 10 98.95 99.14 98.26 Comparative Example 1 99.84 97.55 86.20 Comparative Example 2 95.15 98.03 85.95
[0115] From the data analysis in Table 1:
[0116] It can be seen from the data comparison of Comparative Example 2 and Example 7 that, with polytetrafluoroethylene film as carrier, sodium sulfate solid particles are loaded and reacted in the micropores of polytetrafluoroethylene film, the obtained sodium fluorosilicate crystal purity is up to 99.97%, the utilization rate of fluorosilicic acid is up to 99.76%, and the utilization rate of sodium sulfate is up to 99.10%, which is much higher than the result of the direct participation of sodium sulfate solid particles in the reaction in Comparative Example 2. The reason is that the sodium sulfate solid particles directly participate in the reaction, and the crystallization process has seen the phenomenon of sodium fluorosilicate crystallization wrapping sodium sulfate, which not only causes the sodium fluorosilicate purity to decrease, but also causes the low utilization rate of sodium sulfate. The present invention uses hydrophilic polytetrafluoroethylene film as carrier, sodium sulfate solid particles are loaded and reacted in the micropores of polytetrafluoroethylene film, and the hydrophilicity of polytetrafluoroethylene film enables the reaction medium aqueous solution to fully enter the micropores, dissolves a part of sodium sulfate particles and enters the solution to participate in the reaction, plays the role of slow-release sodium sulfate, and avoids solid sodium sulfate from directly participating in the reaction. In addition, the pore size of the polytetrafluoroethylene membrane is 0.5-15µm, and part of the fluorosilicic acid that enters the micropores may directly react with sodium sulfate to form sodium fluorosilicate, and the micropores of 0.5-15µm can effectively inhibit the crystallization of sodium fluorosilicate. Therefore, the scheme of the present invention is adopted to carry out secondary reaction crystallization, and the polytetrafluoroethylene membrane is used as a carrier to allow solid sodium sulfate to directly participate in the reaction, which not only reduces the amount of wastewater discharge, but also avoids the phenomenon of easy crystallization, and improves the product purity and the utilization rate of fluorosilicic acid and sodium sulfate.
[0117] From the comparison of the data of Comparative Example 1 and the data of Example 7, it can be seen that directly using sodium sulfate liquid for a single reaction crystallization has a high sodium sulfate unit consumption and a utilization rate of only 86.2%, which is much lower than that of Example 7. In addition, liquid sodium sulfate will produce more wastewater.
[0118] It can be seen from the data of Examples 5-7 that the conditions in Example 7 are the best choice.
[0119] From the data comparison of Examples 7-10, it can be seen that the sodium sulfate solid particle load and polytetrafluoroethylene membrane prepared by the method conditions in Example 3 are the best choice. In the cross-linking solution, the hydroxyl group of the hydrophilic polyethylene glycol and the amino group in the polyethylene imine react with acetal and Schiff base respectively with acetone, and a cross-linked hydrophilic network is generated in situ on the hollow fiber of the polytetrafluoroethylene membrane, which is entangled on the fiber and node surface. The primary amine group from the polyethylene imine then undergoes a ring-opening reaction with the hydrolyzed and condensed KH560 to form a nano hydrophilic layer, which is stably attached to the polytetrafluoroethylene fiber. The modified polytetrafluoroethylene membrane has excellent hydrophilicity and water permeability, which is conducive to the reaction medium aqueous solution entering the micropores to dissolve and precipitate sodium sulfate to participate in the reaction. In addition, the temperature of the cross-linking reaction is preferably 30-38°C, and the reaction time is preferably 0.5-3h. If the temperature is too low, the reaction is too slow, which is not conducive to the cross-linking of polyethylene glycol and polyethylene imine on the fiber membrane. If the temperature is too high, the reaction is too fast, resulting in acetone self-polymerization in the solution before entering the membrane pores. If the reaction time is too long, the hydrophilic groups adsorbed on the membrane surface will be too saturated, resulting in the pores of the membrane being blocked or the pore size being too small; if the reaction time is too short, the reaction will be insufficient, the hydrophilic groups on the membrane surface will be reduced, and the hydrophilic properties will be affected.
[0120] In the device of the present invention, sodium sulfate solution is first used in the primary reaction crystallization pool to perform crystallization at 25-50°C, which can make most of the fluorosilicic acid react to form a saturated liquid in a relatively fast time, leaving a small amount of fluorosilicic acid; then the temperature is lowered to perform secondary crystallization at 5-20°C, which is conducive to crystallization conversion and reduces the concentration of fluorosilicic acid after the crystallization reaction. The stirrer in the secondary reaction crystallization pool rotates slowly to drive the solution flow, which can further promote the flow of the solution in the micropores of the polytetrafluoroethylene membrane and improve the utilization rate of sodium sulfate.
[0121] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0122] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing sodium fluorosilicate from hydrofluoric acid produced as a byproduct of wet-process phosphoric acid, characterized in that: The following steps are involved: Centrifuge the fluorosilicic acid solution produced as a byproduct of wet-process phosphoric acid to remove solid particles, and then adjust the fluorosilicic acid solution after centrifugation to a fluorosilicic acid mass concentration of 15-25%; Mixing the fluorosilicic acid solution with the sodium sulfate solution for a first reaction crystallization, wherein the molar ratio of fluorosilicic acid to sodium sulfate is 1:0.95-1.15; After the primary reaction crystallization is completed, a polytetrafluoroethylene membrane loaded with sodium sulfate particles is placed to continue the secondary reaction crystallization, wherein the polytetrafluoroethylene membrane loaded with sodium sulfate particles is prepared by an impregnation method, and the amount of sodium sulfate particles added is: the molar ratio of fluorosilicic acid to sodium sulfate is 1:0.15-0.5; the preparation method of the polytetrafluoroethylene membrane loaded with sodium sulfate particles is as follows: a polytetrafluoroethylene membrane with a pore size of 0.5-15 μm is placed in a saturated sodium sulfate solution at 50-80° C., immersed for 1-72 hours, and then the polytetrafluoroethylene membrane is taken out and dried to obtain a sodium sulfate particle loading of 100-500 g / m 2 ; The polytetrafluoroethylene with a pore size of 0.5-15 μm is a modified hydrophilic fiber membrane; The polytetrafluoroethylene membrane is taken out and recycled, and the filtrate and sodium fluorosilicate are obtained by centrifugation.
2. The method according to claim 1, characterized in that The polytetrafluoroethylene membrane is a modified hydrophilic fiber membrane, and the modification process is as follows: S1, dissolving polyethylene glycol in water, and stirring to obtain a polyethylene glycol aqueous solution; S2. Add polyethyleneimine dropwise to the polyethylene glycol aqueous solution while stirring at 50-80° C., wherein the molar ratio of polyethylene glycol to polyethyleneimine is 5-1:1, and continue stirring for 0.5-2 h after the addition is complete; S3, placing the polytetrafluoroethylene hollow fiber membrane from which impurities have been removed into a mixed solution of polyethylene glycol and polyethyleneimine, and leaving it to stand for 1-5 hours; S4, placing the polytetrafluoroethylene fiber membrane obtained in step S3 into a solution consisting of acetone, acetic acid, nitric acid, ethanol and deionized water, and reacting at 30-38° C. for 0.5-3 h; S5. Take out the polytetrafluoroethylene fiber membrane obtained in step S4 and clean it ultrasonically with deionized water.
3. The method according to claim 2, characterized in that In the liquid consisting of acetone, acetic acid, nitric acid, ethanol and deionized water, the mass fraction of acetone is 1-3%, the mass fraction of acetic acid is 2-8%, the mass fraction of nitric acid is 0.1-1% and the mass fraction of ethanol is 5-10%.
4. The method according to claim 2, characterized in that: The modification process further includes step S6, immersing the polytetrafluoroethylene fiber membrane obtained in step S5 in a KH560 solution with a mass fraction of 1-5%, reacting at 38-50° C. for 1-5 hours, taking out, washing with deionized water and drying to obtain the hydrophilic fiber membrane.
5. The method according to any one of claims 1 to 4, characterized in that: The crystallization temperature of the primary reaction is 25-50°C, and the reaction time is 10-100 min; the crystallization temperature of the secondary reaction is 5-20°C, and the reaction time is 10-60 min.
6. The method according to claim 5, characterized in that The polytetrafluoroethylene film does not need to be cleaned when it is recycled and reused, and can be directly immersed in a saturated sodium sulfate solution to circulate again for secondary reaction crystallization.
7. The method according to claim 6, characterized in that The method further comprises recycling the filtrate to perform a cyclic reaction again, specifically, when the concentration of the fluorosilicic acid solution produced as a byproduct of wet-process phosphoric acid is too high, adding the filtrate to adjust the concentration of the fluorosilicic acid solution after centrifugation.
8. A device for preparing sodium fluorosilicate from by-product fluorosilicic acid of wet-process phosphoric acid, characterized in that: Used to perform the method according to any one of claims 1 to 7; The device comprises an acid treatment component, a primary reaction crystallization tank, a secondary reaction crystallization tank, a centrifugal separation component and a filtrate recovery component which are connected in sequence. The acid treatment component comprises a fluosilicic acid solution regulating tank and a sodium sulfate solution preparing tank, the fluosilicic acid solution is used to regulate the fluosilicic acid solution after centrifugation so that the fluosilicic acid mass concentration is 15-25%, the sodium sulfate solution preparing tank is used to prepare the sodium sulfate solution, and the fluosilicic acid solution regulating tank and the sodium sulfate solution preparing tank are respectively connected to the primary reaction crystallization tank; The primary reaction crystallization pool is used for mixing the fluorosilicic acid solution with the sodium sulfate solution to perform primary reaction crystallization; The secondary reaction crystallization pool is used to place a polytetrafluoroethylene membrane loaded with sodium sulfate particles into the mixed solution after the primary reaction crystallization, and continue the secondary reaction crystallization; the secondary reaction crystallization pool is a cylindrical structure, and a stirrer, a cooling device, a thermometer and a plurality of fixed plates are arranged inside the pool wall; the plurality of fixed plates are arranged on the inner side of the pool wall for laying and fixing the polytetrafluoroethylene membrane, and the fixed plates are a mesh structure of 80-100 meshes; the stirring speed of the stirrer is 1-40rpm; The centrifugal separation component is used to separate the mixed liquid flowing out of the secondary reaction crystallization pool to obtain filtrate and sodium fluorosilicate; The filtrate recovery component is in communication with the fluosilicic acid solution regulating tank and is used for recovering and storing the filtrate and / or conveying the filtrate to the fluosilicic acid solution regulating tank.
